Kampanye Kreatif Calon Presiden Anis Baswedan pada Media Sosial TikTok - Nazma, Asa Afifatun; KN, Jamiati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In the era of rapidly developing social media, political campaigns have experienced changes in approach and strategy. Social media is an online medium where users can easily participate, share, create content, which includes blogs, social networks, forums, and virtual worlds. Political campaigns have experienced significant changes on social media, especially on the popular TikTok platform. This research aims to analyze the creative campaign strategy of presidential candidate Anis Baswedan on TikTok. Anis Baswedan's campaign on TikTok succeeded in creating interesting, creative content and interacting with the audience effectively. With an innovative approach, this campaign was able to expand the reach of political messages and gain significant support from young voters. It is important to adapt political campaign strategies to the latest social media trends to achieve success in political communication in the digital era. With a focus on the case study of presidential candidate Anis Baswedan's creative campaign on the TikTok platform, literature analysis was used to investigate literature related to research methods relevant to political campaigns and social media. The research results provide insight into the strategies, tactics, and impact of political campaigns on social media and facilitate a better understanding of interactions between candidates and voters in a digital context.